Qualitative properties of blow-up solutions to some semilinear elliptic systems in non-convex domains. (June 2023) - Esposito, Francesco; Trombetta, Alessandro
Abstract: In this paper we study qualitative properties of boundary blow-up solutions to some semilinear elliptic cooperative systems in bounded non-convex domains. In particular, by a careful adaptation of the celebrated moving plane procedure of Alexandrov–Serrin, we deduce symmetry and monotonicity results for blow-up solutions for this class of systems.